Cytokinins Stimulate Plasmodesmatal Transport in Leaves - Horner, Wilson; Brunkard, Jacob O. (Frontiers in Plant Science, 2021)
Plant cells are connected by plasmodesmata (PD), nanoscopic channels in cell walls that allow diverse cytosolic molecules to move between neighboring cells. PD transport is tightly coordinated with physiology and development, although the range of signaling pathways that influence PD transport have not been comprehensively defined. Several plant hormones, including salicylic acid and auxin, are known to regulate PD transport, but the effects of other hormones have not been established. Here, we provide evidence that cytokinins promote PD transport in leaves. Using a GFP movement assay in the epidermis of Nicotiana benthamiana, we show that PD transport significantly increases when leaves are supplied with exogenous cytokinins at physiologically-relevant concentrations or when a positive regulator of cytokinin responses, AHP5, is overexpressed. We then demonstrate that silencing cytokinin receptors, AHK3 or AHK4, or overexpressing a negative regulator of cytokinin signaling, AHP6, significantly decrease PD transport. These results are supported by transcriptomic analysis of mutants with increased PD transport (ise1–4), which show signs of enhanced cytokinin signaling. We conclude that cytokinins contribute to dynamic changes in PD transport in plants, which we expect will have implications in several aspects of plant biology, including meristem patterning and development, regulation of the sink-to-source transition, and phytohormone crosstalk.